Genetic and Pathogenic Variability among the Indian Isolates of Sporisorium Scitamineum causing Sugarcane Smut - Barnabas, Leonard; Ashwin, N.M.R; Nalayeni, K; Ramesh Sundar, A; Malathi, P; Viswanathan, R (Journal of Sugarcane Research, 2019)
Sugarcane smut caused by Sporisorium scitamineum is one of the major diseases of sugarcane with globalÂ prevalence and economic significance. Over the recent years, smut incidence has been increasing in India, yet there is no much information available on smut pathogen variability of Indian isolates. Hence, in this study, genetic diversity and pathogenic variability among fifty S. scitamineum isolates representing seven major sugarcane growing regions of India were assessed by inter simple sequence repeats (ISSR) analysis and phenotyping of disease severity on differential hosts at field level. ISSR analysis indicated that there is a considerable genetic diversity among these isolates and majority of the isolates clustered based on their geographical origin. However, there was no variation in the bE mating type gene sequences of representative S. scitamineum isolates and also there were no observable differences in the morphology of teliospores, when examined under scanning electron microscope. In the field experiments, significant differences in the percentage of disease incidence were noticed when 30 representative S. scitamineum isolates were inoculated on Co 96007 (smut susceptible cultivar) and accordingly, the isolates were grouped into different virulence categories. A clear discrimination among representative S. scitamineum isolates was evident based on the differential responses of a set of sugarcane varieties. The results of this study suggests that there is a considerable genetic and pathogenic variation among these isolates representing major sugarcane growing regions of India, which could have been effected upon them by the prevailing environmental conditions and the varieties cultivated in the region.